(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Smart grid is a grouping of information and communication technology and intelligent common infrastructure. Talking about smart grid theÂ consumers and suppliers are very much important inorder to manage,monitor and control all energy issuses smartly. Easy instalation and high reliablity data communication over power line carrier is an importantÂ requirment to make a smart grid more constructive than fixed grid system.ThereforeÂ a latest RFID based power line technology has been developed unlike conventional system carrying data through antenna. RFID based power line carrier technology is used for detection and payment inorder to keep up the grid smart. With this technology, power factor correction and maintanance techniques are included inorder to improve the power system stability. Whenever the non-linear load is connected in load side, the proposed system will automatically detect and connect the power factor correction circuit(capacitor bank) for maintain theÂ power factor in consumer side.